Production of bottomonium states in pp collisions at $$\sqrt{s} = 8.16$$ TeV - Moon, Dong Ho; Cho, Sungtae (Journal of the Korean Physical Society, 2021)
We investigate the production of bottomonium states in pp collisions by focusing on their production cross sections as functions of the rapidities and the transverse momenta at various collision energies. Based on the measurements of the Υ(1S) production cross section at √s = 2.76 , 5.02, and 7.0 TeV by the CMS Collaboration, we obtain the production cross section of the Υ(1S) at √s = 8.16 TeV using both the extrapolation method and a fixed order with next-to-leading log (FONLL) analysis. We also use an extrapolation technique to discuss the Υ(2S) and the Υ(3S) production cross sections in pp collisions at √s = 8.16 TeV. We expect our evaluation of the Υ(1S) production cross sections at √s = 8.16 TeV to be helpful in not only understanding those in pp collisions but also studying various effects such as CNM effects in PbPb collisions. Moreover, we hope the production cross sections of Υ(1S) , Υ(2S) , and Υ(3S) estimated here will play important roles as useful references in measuring the nuclear modification factor, R AA , for Υ(1S) , Υ(2S) , and Υ(3S) , which will be available soon from a PbPb collision analysis at √s = 5.02 TeV. KCI Citation Count: 0